Does the Type of Resin Luting Material Affect the Bonding of CAD/CAM Materials to Dentin? - Burcu Dikici; Elif Türkeş Başaran; Esra Can (Dentistry Journal)
Background/Objectives: This study aimed to investigate the microtensile bond strength (µTBS) of composite-based (Cerasmart), polymer-infiltrated (Vita Enamic), and feldspathic (Cerec) CAD/CAM blocks luted to dentin using a dual-cure resin cement (LinkForce), as well as micro-hybrid (G-aenial) and flowable composites (G-aenial Universal Flo), and evaluate the microhardness (HV) of luting materials through the CAD/CAM blocks. Methods: Cerasmart, Enamic, and Cerec were luted to dentin using three luting materials; LinkForce, G-aenial, and Universal Flo (n = 5). For HV, 117 disk-shaped specimens from LinkForce, G-aenial, and Universal Flo (n = 13) were polymerized through 3 mm thick CAD/CAM. Thirty-nine light-cured specimens without CAD/CAM were used as control. Following 24 h storage, the µTBS and HV were evaluated. Data were analyzed using the two-way ANOVA and post hoc Tukey tests (p < 0.05). Results: The µTBS to dentin and HV were significantly influenced by the type of luting material and CAD/CAM material. With all the CAD/CAM materials, LinkForce and Universal Flo exhibited a significantly similar µTBS to that of dentin (p > 0.05). Compared with the control group, all the HV values of the luting materials decreased significantly (p < 0.05). Conclusions: Heavily filled flowable composites exhibit a bonding effectiveness similar to that of dual-cure resin cements. All the luting materials showed similar HV when polymerized through the polymer-infiltrated CAD/CAM material.